Competency Development Of State Civil Apparatus (ASN) Of Planning (Planners) In The Meranti Islands Regency - Muhammad Adil; Fajarwaty Kusumawardhani (Jurnal Niara, 2022)
Reforms in the field of public management have become mainstream in the bureaucracy and governance, especially in terms of regional development planning. Therefore, planners as the spearhead of regional planning is required to be able to meet the qualifications (competence) as human resources in all support systems of government institutions. Competency development is a necessity for planners and should be directed to arrangements that are in accordance with their field of duty. This study fills in the scarcity of research results related to planners in the Meranti Islands Regency, which is the youngest district in Riau Province. Since its division from Bengkalis Regency in 2008, the Meranti Islands Regency has still not been able to show significant progress. The placement of the planners has not been based on its competence. Efforts to develop the competence of the planners have not been carried out systematically and strategically. This has an impact on the planning and budgeting of the Meranti Islands Regency which has not been effective and efficient. Qualitative research methods with SWOT analysis were used to answer research questions and extract data. This approach is needed as an analytical tool to reach the conclusions expected in this study. The results of the study illustrate that planners need to be equipped with training in order to achieve the desired competencies and be able to plan regional development optimally